Generalizations of an asymptotic stability theorem of Bahyrycz, Páles and Piszczek on Cauchy differences to generalized cocycles - SZÁZ, Árpád (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
We prove some straightforward analogues and generalizations of a re- cent asymptotic stability theorem of A. Bahyrycz, Zs. P´ales and M. Piszczek on Cauchy differences to semi-cocycles and pseudo-cocycles introduced in a former paper by the present author. Mathematics Subject Classification (2010): 39B52, 39B82, 20K99, 22A99.